Daylight Design Graphs for Baghdad City Sky - Saleem, Younis Mahmoud (Iraqi Journal of Architecture and Planning, 2018)
Baghdad city constitutes one of the areas have clear sky with complex and ununiform distribution of light in the sky dome. This was one of the explanations why there is few studies concern with daylighting design in clear skies, from there, this research oriented to devise a new method that can assist in achieving the appropriate levels of lighting for interior spaces. The aim of this research is tempted to find a method that can help designers in achieving the appropriate levels of daylight in architectural spaces with different forms and sizes. The annual distribution rate of daylight was calculated for the horizontal surfaces of different orientations and unobstructed horizontal surface Furthermore account the Intensity of sky light and sun light on vertical surfaces of building facades opposite to the windows. Been reached a number of Graphs as protractor used with architectural drawings (horizontal plans and vertical sections), and by adopting of such Graphs, designers can measure the levels of daylight in any points within the space. Applied this method on a number of design characteristics of shape and direct the window and measure its influence in enlightened points within the space as their distance changes away from window. The research found a number of conclusions linked between the predictability of the distribution of daylighting levels within the space and pattern of distribution of windows within its